2013
DOI: 10.1017/s2045796013000516
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of role attainment and impairment in binge-eating disorder and bulimia nervosa: results from the WHO World Mental Health Surveys

Abstract: Background Cross-national population data from the WHO World Mental Health surveys are used to compare role attainments and role impairments associated with binge-eating disorder (BED) and bulimia nervosa (BN). Methods Community surveys assessed 23,000 adults across 12 countries for BED, BN, and 10 other DSM-IV mental disorders using the WHO Composite International Diagnostic Interview. Age-of-onset was assessed retrospectively. Ten physical disorders were assessed using standard conditions checklists. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…Furthermore, in a study of females conducted at primary care and gynecologic clinics throughout the US, BED was associated with worse health-related QoL on all domains of the Medical Outcomes 20-item Study Short-Form Health Survey compared with females without psychiatric disorders 73. In regard to functional disability, BED is associated with impaired role attainment relative to individuals without BED as measured by females with BED (but not males) being less likely to marry and males with BED (but not females) being less likely to be employed 75. On the Sheehan Disability Scale, ~50% of individuals with BED reported some level of role impairment 7.…”
Section: Evidence Base For Factors Not Included As Diagnostic Criteriamentioning
confidence: 95%
“…Furthermore, in a study of females conducted at primary care and gynecologic clinics throughout the US, BED was associated with worse health-related QoL on all domains of the Medical Outcomes 20-item Study Short-Form Health Survey compared with females without psychiatric disorders 73. In regard to functional disability, BED is associated with impaired role attainment relative to individuals without BED as measured by females with BED (but not males) being less likely to marry and males with BED (but not females) being less likely to be employed 75. On the Sheehan Disability Scale, ~50% of individuals with BED reported some level of role impairment 7.…”
Section: Evidence Base For Factors Not Included As Diagnostic Criteriamentioning
confidence: 95%
“…ED are associated with high morbidity and mortality 8,9 . However, most studies to date have exclusively investigated AN and BN or have relied on clinical samples or patient registers that are not representative of individuals with ED in the general population 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In the World Health Organization (WHO) Mental Health Surveys, role impairment based on the Sheehan Disability Scale (SDS), which assesses functional impairment in three domains (work/school, social life/leisure activities and family life/home responsibilities),4 was reported by 46.7% of individuals meeting Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision ( DSM‐IV‐TR ) diagnostic criteria for BED, with 13.2% reporting severe role impairment 2. The WHO surveys also reported that early‐onset BED (ie, onset before completion of one's education) was associated with a reduced likelihood of being married among women and a reduced likelihood of being employed among men 5. On the Work Productivity and Activity Impairment (WPAI) scale,6 individuals who reported binge eating behaviour also reported greater impairment in work productivity and non‐work activities, as well as increased rates of absenteeism than individuals who did not report binge eating 7, 8…”
Section: Introductionmentioning
confidence: 99%